If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y = 2x + 3 Reorder the terms: 5y = 3 + 2x Solving 5y = 3 + 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '5'. y = 0.6 + 0.4x Simplifying y = 0.6 + 0.4x
| 36y^2-25x^2= | | 54x-16x^4= | | 6x^2+28=0 | | 3n+3-2=6n+18 | | 9(n-4)=5n+8 | | 1-7m=50 | | 4x-28.8=x | | 2x^2+16x+36=0 | | 18y=24x-9 | | .3x+.8=-1.3 | | u^2-4uv-21v^2= | | -126=9n | | -12m-20=-2m+4 | | -(8+3x)+5=2x+3 | | 2(x-3.8)=7.6 | | 36x-21-24x=-114 | | -8m-(3m+6)=5 | | 28x^2-8x-3=0 | | y=-(-1)-2 | | 7b-30=p+6 | | 3(-4X+2)+8X-4=18 | | y=-(-5)-2 | | 14x=-7y+21 | | 134=4x+5 | | 9x+4.32=2x+13 | | 4x^4+12x^3-3x^2-26x-15=0 | | -126=9m | | 6m-9=5m+5 | | 134=4x+5(2x-4) | | -(x+5)-(2+5x)+8x=3x-5 | | 1.9t+2.98=.51 | | z-47=-19 |